Implementation of Gratification Reporting Policy in the Context of Corruption Prevention - Mutiara Carina Rizky Artha; Yuga Kusuma Nugraha; Asropi Asropi (Green Publisher Indonesia, 2025)
Corruption crimes that often occur in the public sector, both in the form of bribes, gratuities, and extortion, are increasingly massively involving public officials and private parties. Public officials as civil servants/state administrators have the obligation to report if the gratuities received are vulnerable related to their positions and contrary to their duties or authority. However, according to data on the number of gratuity reports from the Corruption Eradication Commission (KPK), the number of civil servants/state administrators who report gratuities is still relatively minimal. This shows that compliance in submitting gratuity reports has not been fully complied with by civil servants/state administrators. This study aims to analyze the implementation of gratuity reporting policies in efforts to prevent corruption. The research method used is qualitatively descriptive, namely explaining the phenomenon of gratuity reporting with a data collection method through literature studies of various journal publications, gratuity report data and other relevant documents.